FATHER’S ROLES IN JESSI NELSON’S '' I AM SAM '' - Ade Sulfaida Suaib Ladia; Olga Rorintulus; Sarah Kamagi (Program Studi Pendidikan Bahasa Inggris, 2023)
This study is carried to describe the father’s roles depicted by the main character in the movie